Minha biblioteca: avaliação da usabilidade pelos usuários do sistema de bibliotecas da Universidade Federal da Paraíba - Silva, Jeruzalém de Lima (2018)
The purpose of this research was to analyze the usability of My Library, which belongs to the UFPB library system, based on usability attributes, considering the principles of Ease of Learning, Efficiency of Use, Ease of Memory, Low Error Rate and Subjective Satisfaction. It was characterized as a Case Study in the scope of education in interdisciplinary dialogue, using the direct method, under qualitative methodological approach. As a theoretical background, we present the transformations of Information and Communication Technologies (ICTs) and their nexus with the communication and knowledge networks. We had as subjects of the research the users of the system of libraries of the UFPB linked to the Center of Human Sciences, Letters and Arts. Three categories of respondents were used: teachers, students and administrative technicians, being a total of eighty-five participants; divided into twenty-one teachers, forty-nine students and fifteen administrative technicians. We used the following methods of data collection: bibliographic research, documentary research and questionnaire. As a method of data analysis, we used descriptive analysis by general and specific categories. As a result, we have evidenced the overall context of using My Library, identifying the level of user efficiency, analyzing users' performance and satisfaction with My Library, identifying reasons why users are using My Library and propose mechanisms for its use. We conclude that My Library does not have a good frequency of use and that some measures are necessary so that its usability can improve.